2003
DOI: 10.1037/0022-006x.71.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Partner violence before and after individually based alcoholism treatment for male alcoholic patients.

Abstract: This study examined partner violence in the year before and the year after individually based, outpatient alcoholism treatment for 301 married or cohabiting male alcoholic patients and used a demographically matched nonalcoholic comparison sample. In the year before treatment, 56% of the alcoholic patients had been violent toward their female partner, 4 times the rate of 14% in the comparison sample. In the year after treatment, violence decreased significantly to 25% of the alcoholic sample but remained highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 35 publications
(46 reference statements)
9
123
1
1
Order By: Relevance
“…Recently, there have a number of reports that suggest treatment for alcohol dependence is associated with reductions in intimate partner violence (O'Farrell & Choquette 1991;O'Farrell et al 2003;Stuart et al 2003), that this reduction is also apparent for verbal aggression (O'Farrell et al 2000) and that this reduction is observable up to 2 years post-treatment (O'Farrell et al 1999). In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 88%
“…Recently, there have a number of reports that suggest treatment for alcohol dependence is associated with reductions in intimate partner violence (O'Farrell & Choquette 1991;O'Farrell et al 2003;Stuart et al 2003), that this reduction is also apparent for verbal aggression (O'Farrell et al 2000) and that this reduction is observable up to 2 years post-treatment (O'Farrell et al 1999). In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 88%
“…Although recent research shows that treatment of alcoholism is associated with reduced partner violence, 25 this is not always the case. Therefore the clinician should approach both issues concomitantly.…”
mentioning
confidence: 98%
“…Findings also suggest the importance of addressing alcohol use and childhood physical abuse in interventions targeting IPA. Indeed, reductions in drinking following alcohol treatment are associated with corresponding declines in IPA (O'Farrell, Fals-Stewart, M. Murphy, & Murphy, 2003). Although an individual's history of childhood physical abuse cannot be changed, these early experiences may promote violence-supportive beliefs that interfere with later conflict resolution skills.…”
Section: Discussionmentioning
confidence: 99%